What is Understanding By Design (UbD)? - Tyler L. D'Angelo; Andrew C. Thoron; James C. Bunch (EDIS)
This 5-page document discusses Understanding by Design, an approach to designing curriculum that allows instructors to focus on desired learning outcomes and provide structure for student learning. Written by Tyler L. D’Angelo, Andrew C. Thoron, and J. C. Bunch and published by the UF/IFAS Department of Agricultural Education and Communication, January 2019. http://edis.ifas.ufl.edu/wc322